Zambia : Selected Issues. (IMF Staff Country Reports; Country Report, 2008)
This paper analyzes the efforts taken to create fiscal space for the implementation of the fifth national development plan and the risk associated with it, examines the role of monetary policy in determining inflation, and discusses policy options to achieve low inflation. It also identifies areas where reform strategy needs more attention and suggests that reforms of financial system regulation need to be accelerated to ensure stability of the system. It analyzes traditional reserve adequacy measures, and finds looming power crisis as an obstacle to growth.